PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Hardi, Andhimas Bayu Rezky; Kurniawati, Desi Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the simultaneous and partial influence related to work motivation and work discipline on the performance of employees of PT Bank Perkreditan Rakyat Tanjung Tani. This research uses quantitative methods with explanatory research. The study also used instrument tests, classical assumptions, and multiple linear regression. The population in this study was 50 people and used a saturated sampling technique for all employees at PT Bank Perkreditan Rakyat Tanjung Tani which amounted to 47 employees. The data analysis tool used is SPSS Statistics 25.0 in the form of multiple linear regression analysis, as well as hypothesis testing through t test, F test and coefficient of determination test. The results of this study show that the variables Work Motivation (X1) and Work Discipline (X2) have a simultaneous influence on Employee Performance (Y). As for partially, Work Motivation (X1) has a significant influence on employee performance (Y) of PT Bank Perkreditan Rakyat Tanjung Tani. The results of this study also showed that partially the Work Discipline variable (X2) did not have a significant influence on employee performance (Y) of PT Bank Perkreditan Rakyat Tanjung Tani.